Systems biology of parkinson's disease - Cloutier, Mathieu; Wellstead, Peter (Springer New York, 2012)
This text is the first to present a study of Parkinson's disease from a Systems Biology perspective. By placing the condition at centre stage, the authors have been able to provide a wide ranging modelling and systems analysis that is focussed on a multi-facetted and highly complex condition. The book comprises a specially selected set of eight studies of important aspects of PD, covering all relevant scales of space and time. These are used to show how innovative sensing techniques, mathematical modelling, model analysis and computational simulation can throw new light on the dynamics of disease mechanisms that drive this important form of neurodegeneration.